Analysis of a Microgrid under Transient Conditions Using Voltage and Frequency Controller. (9th December 2012) - Jain, Monika; Gupta, Sushma; Masand, Deepika; Agnihotri, Gayatri
Abstract : This paper presents an investigation of voltage-and-frequency-(VF-) based battery energy storage system (BESS) controller used in micro grid for analyzing the optimum capability of plant. Microgrid is formed by using three hydropower plants feeding three-phase four-wire load. The proposed controller is used for load balancing, harmonic elimination, load leveling, and neutral current compensation. The proposed BESS controller permits the selection of an optimum voltage level of battery and allows independent current control of each phase. The main emphasis is given on maintaining constant voltage and frequency within the micro grid during transient conditions. Micro grid with power plant and its controller is modeled in MATLAB/Simulink using Power System Blockset (PSB) toolboxes.